A new blow-up criterion of the strong solution to the quantum hydrodynamic model. (September 2021) - Wang, Guangwu; Guo, Boling
Abstract: In this paper, we establish a new blow-up criterion of the strong solution to the quantum hydrodynamic model. This blow-up criterion is different from the one established in our former paper (Wang and Guo, 2020). This blow-up criterion only depends on the gradient of the velocity, but also the first order time derivative of the square root of the density.